STUDI KOMPARATIF PETANI BERMITRA DAN TIDAK BERMITRA PADA USAHATANI CABAI MERAH DI DESA WONOASRI KECAMATAN TEMPUREJO KABUPATEN JEMBER - Ghea Masitha Nanda Lestari; Lenny Widjayanthi; Ati Kusmiati (University of Jember, 2016)
Red chili is a vegetable commodity that is much needed, not only domestic needs but also abroad. District of Tempurejo Wonoasri Village area is an area where there is a group of farmers who namely farmers partnership and not partnership. The goal of study are: (1) Examines the factors which to base decisions for partnership and not partnership farmer. (2) Examines the income disparities for partnership and not partnership farmer. (3) Examines the factors that effect a level of income for partnership and not partnership farmer. The method used descriptive analysis method and comparative analysis method. This research used primary data and secondary data. The analysis method used priority setting analysis, income approach, and multiple linear regression analysis. The result of study shows that: (1) The order of priority factors for partnership farmers are: Indemnity risk; Capital guarantee; Market; Availability of fertilizer; The cultivation technical guidance; Post-harvest technical guidance; Government involvement; Planting certain varieties; and The openness of the employers. The order of priority factors that farmers do not partner are: The openness of the employers; Planting certain varieties; Government involvement; Availability of fertilizer; Post-harvest technical guidance; The cultivation technical guidance; Capital guarantee; Indemnity risk; and Market. (2) Average income of non-partner farmers and growers partners on red chili farming in the village Wonoasri is not significantly different, (3) factors that affect farmers' income levels are partnership and partnership is a production, the cost of soil lease, and farmers' membership status.